Anatomic Considerations of the Distal Fibula: A Computed Tomography Guided Analysis. Issue 1 (January 2022) - Locker, Philip H.; Waldman, Leah; Michalski, Max
Category: Ankle; Basic Sciences/Biologics; Trauma; Other Introduction/Purpose: Ankle fractures are a common injury in the general population with nearly sixty thousand operations performed in California for fractures involving the tibiotalar joint over a 10-year span. Reestablishing anatomic fibular alignment after fracture reduction leads to improved patient outcomes by restoring ankle mortise congruence. An in-depth understanding of fibular morphology may aid in fracture reduction, preoperative planning, plate positioning and intra-operative contouring. The goal of this study is to perform quantitative morphologic analysis of distal fibular anatomy using computed tomography (CT). Methods: Using Nuance mPower Clinical Analytics software, a database of CT tibia-fibula reports for patients ages 18 through 35 performed at our institution were searched for the term 'normal.' Inclusion criteria was absence of any reported osseous pathology. Examinations were excluded if the fibula was incompletely imaged. Twenty CTs were collected and analyzed. Measurements were performed at 5 mm increments from the tip of the fibula extending proximally to 10 cm. At each level the following measurements were obtained: lateral and posterior border lengths, lateral to medial (LM) bicortical distances at ¼, ½, and ¾ the length of the lateral border, posteroanterior (PA) bicortical distance at the center of the posterior border, and the angles of the lateral and posterior borders relative to the PA axis of the tibia (figure 1). The location of the maximal bicortical distance in the LM direction was recorded at each level. Results: The posterior border of the fibula broadens from an apex distally to 8.4+-1.6 mm at 10 cm proximal while rotating an average of 97.5 degrees. The lateral border of the fibula rotates 6.3 degrees from distal to proximal and begins with a width of 12.8+-3.1 mm and comes to an apex at 9 cm. In the distal fibula, the ratio of the maximal LM to PA bicortical length is 0.56. By 3 cm proximal, the ratio approaches 1 and is 1.6 at 10 cm. The distal 1 cm of the fibula has the largest LM diameter anteriorly and medially but from 1.5 cm to 10 cm proximal the posterior ¼ has the largest LM diameter. Conclusion: The fibula has a complex distal geometry which changes with progression from the distal tip to 10 cm proximal. The posterior border of the fibula broadens and rotates over 90 degrees to become the lateral border proximally. The lateral border distally is broad but comes to an apex proximally with minimal rotation. The ratio of bicortical distances changes from distal to proximal as the distal posterior border rotates to face in a LM direction proximally. This information may aid in surgeons' understanding of the complex distal fibular morphology and assist with intra-operative decision making regarding hardware size, placement and manipulation.